Articulação de uma plataforma de experiência para engajamento: estudo da plataforma digital MyMagic+ da Disney - Martins, Fabrício Almeida Brandão (2017)
This dissertation has as main research goal the design of the perceptive experience for structuring a platform of experience configured to promote the engagement between people and companies in large scale. For this, it features a MyMagic+, digital platform that connects all Disney attractions and narratives, promoting a comprehensive, engaging and irresistible experience. Making a counterpoint to marketing yearnings according to a vision of marketing executives and thinkers such as Steven J. Heyer, Kevin Roberts, Lee Cockerell, and Philip Kotler, this research addresses subjects such as experience, media, design, synaesthesia, and engagement through authors Like Merleau-Ponty, Maturana and Varela, McLuhan and Jenkins, an interdisciplinary analysis necessary also includes concepts worked by Donald Norman, emotional design researcher and game designer Scott Rogers. They are analyzed as perceptions of magic and dream described by Disney consumers, the importance of constructing a utopian thematic world, a technical articulation of the means for a configuration of desires and the role of affectivity in the interaction, always with a view to understanding what is engagement and the role of a platform in technology-mediated engagement